Efektivitas Promosi Kesehatan Cuci Tangan oleh peer group terhahap Pelaksanaan Perilaku Hidup Bersih dan Sehat di Pesantren Imam Syafi’iy Kota Bima - Ayatullah, Ayatullah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The first indicator of the success of implementing PHBS in educational institutions is being able to practice the behavior of washing hands with soap to prevent the onset of disease. Islamic boarding schools are educational institutions where students live in cottages for 24 hours. The habit of not washing hands with soap makes students easily infected with diseases such as acute respiratory infections and diarrhea. Especially in the current pandemic era. To find out the effectiveness of handwashing health promotion by peer groups on the implementation of clean and healthy living behaviors at the Imam Syafi'iy Islamic Boarding School, Bima City. This research uses a pre-experimental type of research with a one group pretest-posttest design. The research sample was 38 junior high school female students who lived at the Imam Syafi'iy Islamic Boarding School. The results of the study were 38 respondents, before being given hand washing health promotion by the peer group, most of the respondents had less hand washing habits, 16 students (42.1%), after being given hand washing health promotion by the peer group, most of the respondents had a hand washing habit. well, 26 students (68.4%). The Wilcoxon statistical test shows p-value = 0.000 < α (0.05). There is the effectiveness of hand washing health promotion by peer groups on the implementation of clean and healthy living behaviors at the Imam Syafi'iy Islamic Boarding School, Bima City.